Microfluidic-Prepared, Monodisperse, X-ray-Visible, Embolic Microspheres for Non-Oncological Embolization Applications - Beh, Cyrus W. (Lab Chip, 2020)
Embolotherapy using particle embolics is normally performed with exogenous contrast to assist in visualization. However, the exact location of the embolics cannot be identified after contrast washout. We developed a novel, pseudo-check valve-integrated microfluidic device, that partitions barium-impregated alginate from crosslinking solution, thereby preventing nozzle failure. This enables rapid and continuous generation of inherently X-ray-visible embolic microspheres (XEMs) with uniform size. The XEMs are visible under clinical X-ray and cone beam CT both in vitro and in vivo. In particular, we demonstrated the embolization properties of these XEMs in large animals, performing direct intra- and post-procedural assessment of embolic delivery. The persistent radiopacity of these XEMs enables real-time evaluation of embolization precision and offers great promise for non-invasive follow-up examination without exogenous contrast. We also demonstrated that bariatric arterial embolization with XEMs significantly suppresses weight gain in swine, as an example of a non-oncological application of embolotherapy.